1996
DOI: 10.1210/endo.137.7.8770888
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I and insulin down-regulate growth hormone (GH) receptors in rat osteoblasts: evidence for a peripheral feedback loop regulating GH action.

Abstract: The anabolic actions of GH are mediated by the production of insulin-like growth factor I (IGF-I) from the liver and by local production of IGF-I in extrahepatic tissues. Insulin facilitates the hepatic production of IGF-I by up-regulating GH receptors (GHRs) in the liver and augmenting the IGF-I response to GH. Although GHRs have also been identified in extrahepatic tissues that produce IGF-I, the possibility that IGF-I and insulin might partake in GHR regulation, thereby modulating the effects of GH locally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…These observations are consistent with IGF-I's promoting osteoblast differentiation. IGF-I has been shown to stimulate proliferation in numerous osteoblast-like model systems [10][11][12][13][14][15][16][17]. The present studies present an apparent paradox in the effect of rhIGF-I on stimulating DNA synthesis and decreasing lag time while slowing the maximal growth rate attained by an osteoblast strain and altering extracellular matrix expression.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These observations are consistent with IGF-I's promoting osteoblast differentiation. IGF-I has been shown to stimulate proliferation in numerous osteoblast-like model systems [10][11][12][13][14][15][16][17]. The present studies present an apparent paradox in the effect of rhIGF-I on stimulating DNA synthesis and decreasing lag time while slowing the maximal growth rate attained by an osteoblast strain and altering extracellular matrix expression.…”
Section: Discussionmentioning
confidence: 55%
“…The most frequently reported effect of IGF-I on osteoblast-like cells in itro has been the stimulation of cellular proliferation. Proliferation was increased by IGF-I in MC3T3-E1 cells [10], the human OHS-4 cell line [11], the human TE89 cell line [12], MG63 osteosarcoma cells [13], SAOS-2 cells [14], UMR 106-06 cells [15] and primary fetal rat calvaria cells [16]. IGF-I stimulated, in a dose-and time-dependent manner, the specific activity of creatine kinase (a marker of skeletal cell division) in both female and male rat calvarial bone cells, in ROS 17\2.8 cells and in epiphyseal cartilage cell cultures [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that the higher expression of GHR is GH receptor expression on human lymphocytes 333 ᭧ 1997 Blackwell Science Ltd, Clinical Endocrinology, 47, 329-335 found in subjects who are growing slowly (Group A and B short children) or not at all (adults). The upregulation of GHR might be induced (Leung et al, 1996) by the lower GH levels or the lowered IGF-1 levels, which have been reported in adults (Zadik et al, 1985) and idiopathic short children (Carlsson et al, 1994). Despite the fact that stimulated GH peaks were above the arbitrary cut-off level of 10 mg/l (20 mU/l) in Group A patients, however, no significant difference in GHR expression was found between these patients and Group B children, in whom peak GH levels were < 10 mg/l (20 mU/l).…”
Section: Discussionmentioning
confidence: 99%
“…Curve B demonstrates normal bone mass maintenance, but failure to acquire a normal peak bone mass. osteoblasts and to interfere with GH receptor function (in rats), suggesting a local feedback loop [34,35].…”
Section: Gh and The Maintenance Of Bone Massmentioning
confidence: 99%